AKIBAT HUKUM WASIAT YANG BERISI PENUNJUKAN AHLI WARIS DAN HIBAH WASIAT MENURUT KITAB UNDANG-UNDANG HUKUIM PERDATA - Adi Putra Pratama (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2015)
Abstract : Thesis entitled as a â€œRESULT OF LAW THAT WILL CONTAIN THE APPOINTMENT AND GRAND TESTAMENTARY HEIR ACCORDING TO THE BOOK OF THE CIVIL LAWâ€. Discuss issues of legal issues that result of law that will contain the appointment and grant testamentary heir according to the book of the civil law; in heritance right to the heirs by statutory (ab intestato) and testament which contains appointment heirs (erfstelling) according to the laws of civil law. Theoretical basis used in this study is the theory of the rule of law, rights theory and theory of legal protection. This type of research uses type of normative legal research using regulatory approach and conceptual approach. Materials research in this thesis the primary law, secondary and tertiary, which is processed at the level of technical level, the level of teleological and systematic level of internal. Material analysis carried out by method of interpretation of law contruction. Based method of deductive logic to think that we can conclude about testamentary appointment and grant testamentary heirs and logical qonsecuences according to the book of civil law by looking article 954 and 957 of the book. However, due to legal provisions regarding the appointment of a will that contains a grant heirs and testament in the book of the law of civil law. The next concept of the ideal law which must be applied by a public official or for a notary clarity and legal certainly. On the rights of heirs either by statute (ab intestato) or by the law of will and grants means that in the future there is no problem or dispute after heiress dies.   KeyWords: Heiress, Wealth, Heir, Grant Will , Will Containt The Appointment (erfstelling), Grant Testamentary (legaat)